IRF5 regulates unique subset of genes in dendritic cells during West Nile virus infection - Chow, Kwan T. (J Leukoc Biol, 2018)
Pathogen recognition receptor (PRR) signaling is critical for triggering innate immune activation and the expression immune response genes, including genes that impart restriction against virus replication. RIG-I-like receptors and Toll-like receptors are PRRs that signal immune activation and drive the expression of antiviral genes and the production of type I interferon (IFN) leading to induction of IFN-stimulated genes, in part through the Interferon Regulatory Factor (IRF) family of transcription factors. Previous studies with West Nile virus (WNV) showed that IRF3 and IRF7 regulate IFN expression in fibroblasts and neurons, whereas macrophages and dendritic cells (DCs) retained the ability to induce IFNβ in the absence of IRF3 and IRF7 in a manner implicating IRF5 in PRR signaling actions. Here we assessed the contribution of IRF5 to immune gene induction in response to WNV infection in DCs. We examined IRF5-dependent gene expression and found that loss of IRF5 in mice resulted in modest and subtle changes in the expression of WNV-regulated genes. Anti-IRF5 chromatin immunoprecipitation with next-generation sequencing of genomic DNA coupled with mRNA analysis revealed unique IRF5 binding motifs within the mouse genome that are distinct from the canonical IRF binding motif and that link with IRF5-target gene expression. Using integrative bioinformatics analyses, we identified new IRF5 primary target genes in DCs in response to virus infection. This study provides novel insights into the distinct and unique innate immune and immune gene regulatory program directed by IRF5.